Используя формулу разности квадратов
Домножив и разделив на 1 или то же самое что а-в, получим
\\\\ (a^4-b^4)(a^4+b^4)...(a^{64}+b^{64}) =...=\\\\ (a^{64}+b^{64})(a^{64}-b^{64})=a^{128}-b^{128}" alt="(a+b)(a^2+b^2).....(a^{64}+b^{64})=(a+b)(a^2+b^2).....(a^{64}+b^{64})(a-b):1=\\\\(a+b)(a-b)(a^2+b^2).....(a^{64}+b^{64})=\\\\ (a^2-b^2)(a^2+b^2).....(a^{64}+b^{64})=\\\\ (a^4-b^4)(a^4+b^4)...(a^{64}+b^{64}) =...=\\\\ (a^{64}+b^{64})(a^{64}-b^{64})=a^{128}-b^{128}" align="absmiddle" class="latex-formula">. Доказано